Assessing learner's Scientific Inquiry Skills across time: A Dynamic Bayesian Network approach - Ting, Choo-Yee; Mohammad Reza Beik, Zadeh (2007)
In this article, we develop and evaluate three Dynamic Bayesian Network (DBN) models for assessing temporally variable learner scientific inquiry skills (Hypothesis Generation and Variable Identification) in INQPRO learning environment. Empirical studies were carried out to examine the matching accuracies and identify the models' drawbacks. We demonstrate how the insights gained from a preceding model have eventually led to the improvement of subsequent models. In this study, the entire evaluation process involved 6 domain experts and 61 human learners. The matching accuracies of the models are measured by (1) comparing with the results gathered from the pretest, posttest, and learner's self-rating scores; and (2) comments given by domain experts based on learners' interaction logs and the graph patterns exhibited by the models.